Involvement of a putative intercellular signal-recognizing G protein-coupled receptor in the engulfment of Salmonella by the protozoan Tetrahymena - P.N. Agbedanu; M.T. Brewer; T.A. Day; M.J. Kimber; K.L. Anderson; S.K. Rasmussen; M.A. Rasmussen; S.A. Carlson (Open Veterinary Journal, 2013)
In an effort to investigate the molecular basis of protozoa engulfment-mediated hypervirulence of Salmonella in cattle, we evaluated protozoan G protein-coupled receptors (GPCRs) as transducers of Salmonella engulfment by the model protozoan Tetrahymena. Our laboratory previously demonstrated that non-pathogenic protozoa (including Tetrahymena) engulf Salmonella and then exacerbate its virulence in cattle, but the mechanistic details of the phenomenon are not fully understood. GPCRs were investigated since these receptors facilitate phagocytosis of particulates by Tetrahymena, and a GPCR apparently modulates bacterial engulfment for the pathogenic protozoan Entamoeba histolytica. A database search identified three putative Tetrahymena GPCRs, based on sequence homologies and predicted transmembrane domains, that were the focus of this study. Salmonella engulfment by Tetrahymena was assessed in the presence of suramin, a non-specific GPCR inhibitor. Salmonella engulfment was also assessed in Tetrahymena in which expression of putative GPCRs was knocked-down using RNAi. A candidate GPCR was then expressed in a heterologous yeast expression system for further characterization. Our results revealed that Tetrahymena were less efficient at engulfing Salmonella in the presence of suramin. Engulfment was reduced concordantly with a reduction in the density of protozoa. RNAi-based studies revealed that knock-down of one the Tetrahymena GPCRs caused diminished engulfment of Salmonella. Tetrahymena lysates activated this receptor in the heterologous expression system. These data demonstrate that the Tetrahymena receptor is a putative GPCR that facilitates bacterial engulfment by Tetrahymena. Activation of the putative GPCR seemed to be related to protozoan cell density, suggesting that its cognate ligand is an intercellular signaling molecule.